2002
DOI: 10.1161/01.cir.0000023620.59633.53
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Imaging of Cardiac Reporter Gene Expression in Living Rats

Abstract: Background — Imaging reporter gene expression is useful for noninvasive monitoring of gene therapy. In this study, we imaged cardiac reporter gene expression in living rats using micro positron emission tomography (microPET). Methods and Results — Rats (n=10) underwent intramyocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
101
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 10 publications
3
101
0
1
Order By: Relevance
“…Recently, we demonstrated the feasibility of imaging the location, magnitude, and duration of a single PET (positron emission tomography) reporter gene (HSV1-sr39tk) expression in the myocardium of living rats using a dedicated small-animal microPET with high spatial resolution (2 mm 3 compared with 6 mm 3 for clinical PET). 10,11 We subsequently showed that the expression of 2 PET reporter genes (HSV1-sr39tk and mutant dopamine 2 receptor) linked together by an internal ribosomal entry site had good correlations in both cell assays (rϭ0.98, PϽ0.001) and rat myocardium (rϭ0.86, PϽ0.001). 12 Therefore, the present study is a logical progression of our previous works on cardiac gene imaging.…”
mentioning
confidence: 99%
“…Recently, we demonstrated the feasibility of imaging the location, magnitude, and duration of a single PET (positron emission tomography) reporter gene (HSV1-sr39tk) expression in the myocardium of living rats using a dedicated small-animal microPET with high spatial resolution (2 mm 3 compared with 6 mm 3 for clinical PET). 10,11 We subsequently showed that the expression of 2 PET reporter genes (HSV1-sr39tk and mutant dopamine 2 receptor) linked together by an internal ribosomal entry site had good correlations in both cell assays (rϭ0.98, PϽ0.001) and rat myocardium (rϭ0.86, PϽ0.001). 12 Therefore, the present study is a logical progression of our previous works on cardiac gene imaging.…”
mentioning
confidence: 99%
“…The former has been specifically validated for cardiac applications 10 ; we now report the first use of the latter system specifically for myocardial imaging. Compared with HSV1-sr39tk, D2R80a has the advantage of being endogenous and therefore should elicit minimal immune response and lead to prolonged adenovirus-mediated transgene expression in rat myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously succeeded in monitoring adenovirus-mediated reporter gene expression in immunocompetent rats for Ϸ2 weeks, but not much longer because of the mounting of an intense host immune response. 10 To examine the behavior of Ad-CMVD2R80a-IRES-HSV1-sr39tk for a much longer period, we used athymic rats in this study to minimize immune response while simulating the case clinically when the subject is immunosuppressed. We then repeated experiments in immunocompetent rats to investigate whether host immune response would alter IRES-mediated translation or specifically the coupling between the expressions of HSV1-sr39tk and D2R80a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations